Pengembangan Sistem Repositori Jurnal Berbasis Web Menggunakan Metode Agile dan Framework Yii: Pengembangan Sistem Repositori Jurnal Berbasis Web Menggunakan Metode Agile dan Framework Yii - Rahman; Syamsul, Sulfianti (Jurnal INSYPRO (Information System and Processing), 2025)
This research is motivated by the problems in managing research journal drafts in the academic environment, especially among students and supervisors. Currently, journal data storage and processing are still done manually, so supervisors experience difficulties in tracking students' published scientific works. This is caused by the lack of an integrated system for storing and managing the data. This study aims to develop an application that can simplify the process of storing and processing journal data by building a research journal draft repository information system in the Information Systems Study Program. The type of research used is quantitative research with agile software development methods. Data were collected through literature studies and surveys using questionnaires. The developed system was tested using the System Usability Scale (SUS) method. The result of this study is a web-based information system that makes it easier for students and supervisors to store and manage journal data. Based on the results of testing and questionnaire analysis, the system obtained an average SUS score of 83.3 and is included in the "Acceptable" category in the Acceptability Range. These results indicate that the developed research journal draft repository information system is feasible to use and can be implemented well by users.